Gigantic mysticete predators roamed the Eocene Southern Ocean - Marx, Felix G.; Buono, Mónica Romina; Evans, Alistair R.; Fordyce, Robert Ewan; Reguero, Marcelo Alfredo; Hocking, David P. (Antarctic Science)
Modern baleen whales (Mysticeti), the largest animals on Earth, arose from small ancestors around 36.4 million years ago (Ma). True gigantism is thought to have arisen late in mysticete history, with species exceeding 10 m unknown prior to 8 Ma. This view is challenged by new fossils from Seymour Island (Isla Marambio), Antarctica, which suggest that enormous whales once roamed the Southern Ocean during the Late Eocene (c. 34 Ma). The new material hints at an unknown species of the archaic mysticete Llanocetus with a total body length of up to 12 m. The latter is comparable to that of extant Omura´s whales (Balaenoptera omurai Wada et al. 2003), and suggests that gigantism has been a re-occurring feature of mysticetes since their very origin. Functional analysis including sharpness and dental wear implies an at least partly raptorial feeding strategy, starkly contrasting with the filtering habit of living whales. The new material markedly expands the size range of archaic mysticetes, and demonstrates that whales achieved considerable disparity shortly after their origin. Fil: Marx, Felix G. Royal Belgian Institute of Natural Sciences. Directorate Earth and History of Life; Bélgica. Monash University; Australia. Museums Victoria. Geosciences; Australia Fil: Buono, Mónica Romina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto Patagónico de Geología y Paleontología; Argentina Fil: Evans, Alistair R. Monash University; Australia. Museums Victoria. Geosciences; Australia Fil: Fordyce, Robert Ewan. University of Otago; Nueva Zelanda. National Museum of Natural History; Estados Unidos Fil: Reguero, Marcelo Alfredo. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Hocking, David P. Monash University; Australia. Museums Victoria. Geosciences; Australia